Linear Scheduling Method or Line of Balance (LSM/LOB) Scheduling Analysis for Devely Residence Housing, Batam City - Verolio Verolio; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2023)
Project time scheduling is one of the keys to the success of a project. With the project scheduling, project activities can run effectively and smoothly. There are several project scheduling methods commonly used in construction projects. One of them is the Line of balance method. Line of balance method is one of the methods that is suitable on projects that have repetitive work. In this research, the author takes a case study on the Devely Residence housing project in Batam City. There are as many as 220 housing units in this project. From the results of the research conducted, it shows that the Line of Balance method can be used in repetitive projects such as housing in Development Residence. The result shows that by using this method, the 220-unit Devely Residence project can be completed in 349 days. Whereas in real implementation in the field, this project is completed within 365 days. Thus, there is a 16-day difference in project completion.